2021
DOI: 10.1177/00405175211056980
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the airflow field of vortex spinning

Abstract: Vortex spinning technology adopts a high-speed swirling airflow to rotate the fibers with open-ends to form yarn with real twists. The airflow behavior within the nozzle has a great effect on the yarn-formation process. In this study, a three-dimensional calculation nozzle model and corresponding three-dimensional airflow region model were established to enable the numerical calculation; airflow behavior—pressure, velocity, and the turbulent airflow field, and the streamline of airflow—was investigated in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…41,42 The realizable kÀe model has been proved to have significant improvements over the standard kÀe model in handling flows with strong streamline curvature, vortices, and rotations. [43][44][45] The turbulent field was mainly characterized by turbulent kinetic energy and turbulent viscosity, by comparing the two, Shang et al 37 demonstrated that the flow field was more disordered in steady spinning stage than in the initial spinning stage. Shang et al 44 suggested that the presence of the cone body had influenced the dissipation and rupture of the turbulent vortex.…”
Section: Vortex Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…41,42 The realizable kÀe model has been proved to have significant improvements over the standard kÀe model in handling flows with strong streamline curvature, vortices, and rotations. [43][44][45] The turbulent field was mainly characterized by turbulent kinetic energy and turbulent viscosity, by comparing the two, Shang et al 37 demonstrated that the flow field was more disordered in steady spinning stage than in the initial spinning stage. Shang et al 44 suggested that the presence of the cone body had influenced the dissipation and rupture of the turbulent vortex.…”
Section: Vortex Fieldsmentioning
confidence: 99%
“…[43][44][45] The turbulent field was mainly characterized by turbulent kinetic energy and turbulent viscosity, by comparing the two, Shang et al 37 demonstrated that the flow field was more disordered in steady spinning stage than in the initial spinning stage. Shang et al 44 suggested that the presence of the cone body had influenced the dissipation and rupture of the turbulent vortex. High velocity air flow is also compressible.…”
Section: Vortex Fieldsmentioning
confidence: 99%
“…where, j is the jth triangular element; A, B, and C are the three nodes of a triangular unit; / A , / B , and / C are the velocity potentials of the air-flow field at A, B, and C nodes, respectively; x, y, and z are coordinates in rectangular coordinates; n is the unit normal vector. By solving equation (22), the velocity potential gradient of element j can be obtained, and other elements are similarly found.…”
Section: Governing Equationsmentioning
confidence: 99%
“…), but also at the influence of air flow on fiber, the important air-flow fields that affect the fiber were analyzed already in a previous research study. 22 In this article, we provide details of a continuation of previous research, and our main focus is on the characteristics and motion of the fiber.…”
mentioning
confidence: 99%
See 1 more Smart Citation